1997
DOI: 10.1046/j.1365-2427.1997.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐induced shear stresses, plant nutrients and chlorophyll in seven shallow lakes

Abstract: 1. Sediment resuspension dynamics were investigated in relation to changes in water column nutrients (TP, TN, PO4‐P, NO3‐N and NH4‐N), chlorophyll a and phaeopigment in seven shallow (Zm < 1.5 m) lakes in South Island, New Zealand, ranging in area from 0.1 to 180 km2. 2. Benthic shear stress, calculated from wind speed, effective fetch and depth, was a considerably better predictor of nutrient and pigment concentrations than wind speed. 3. For TP, TN, chlorophyll a and phaeopigment, sixteen of the possible twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 5 publications
7
81
1
Order By: Relevance
“…These three lakes appear to provide ideal conditions for the proliferation of C. raciborskii, with high concentrations of nutrients and low water clarity (Table 1). Other shallow lakes in New Zealand which have changed to an "alternative stable state" (Scheffer 1998) signalled by nutrient enrichment, high turbidity, and loss of macrophytes (Hamilton & Mitchell 1997), could also be expected to be susceptible to blooms of C. raciborskii, depending on water temperature. C. raciborskii does not appear to be favoured by a specific thermal stratification regime (Antenucci et al 2002) whereas bloom formation in many other species of cyanobacteria (e.g., Microcystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…These three lakes appear to provide ideal conditions for the proliferation of C. raciborskii, with high concentrations of nutrients and low water clarity (Table 1). Other shallow lakes in New Zealand which have changed to an "alternative stable state" (Scheffer 1998) signalled by nutrient enrichment, high turbidity, and loss of macrophytes (Hamilton & Mitchell 1997), could also be expected to be susceptible to blooms of C. raciborskii, depending on water temperature. C. raciborskii does not appear to be favoured by a specific thermal stratification regime (Antenucci et al 2002) whereas bloom formation in many other species of cyanobacteria (e.g., Microcystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared with other studies, including shallow eutrophic lakes in northern Europe [11][12][13], New Zealand [14] and Estonia and Russia [15], phosphorus and nitrogen in sediments are still low. This may be caused by the large surface area of BMR.…”
Section: -P4mentioning
confidence: 67%
“…Moreover, the variation in Chl-a due to algal growth and death led to transformation and greater dynamics of nutrients in the control. The experimental enclosures were located in shallow water in the windy Lake Erhai, and thus wave-induced resuspension of soft sediment might have contributed to the release of nutrients from the sediment into the water column in the control (Hamilton and Mitchell, 1997), in contrast to the other two treatments with sediment capping, which stabilized the surface sediments (Vopel et al, 2008;Lin et al, 2011). The synchronic changes in DIN, N-NO 3 , N-NH 4 , SRP, SD and K suggested that abiotic factors (i.e., wind-induced waves) were affecting the three treatments simultaneously, in contrast to Chl-a, TN and TP, which were closely related to algal growth and N and P found in the algal biomass, and thus differed significantly between the control and the other two treatments.…”
Section: Discussionmentioning
confidence: 99%